Peran Edukasi Kewirausahaan dalam Meningkatkan Minat Berwirausaha di Kalangan Mahasiswa - Nasir, Nasir (Politeknik Sawunggalih Aji, 2025)
Entrepreneurship education plays an important role in shaping the mindset and increasing students' interest in entrepreneurship. This study aims to analyze the role of entrepreneurship education in increasing entrepreneurial interest among students and identify its supporting and inhibiting factors. This study uses a qualitative approach with a case study method in one of the universities in Indonesia. Data was collected through in-depth interviews, observations, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawn. The results of the study show that practice-based entrepreneurship education, such as business simulations, mentoring, and incubation programs, has a positive impact on increasing students' interest and readiness to start a business. The main supporting factors include institutional support, access to business mentors, and start-up funding facilities, while inhibiting factors include limited practical experience, lack of business networks, and limited access to capital. Therefore, universities are advised to strengthen experiential learning methods and increase collaboration with the business world to create a more conducive entrepreneurial ecosystem.